GROWING ONIONS AS A SECONDARY CROP FROM SEEDLINGS IN UZBEKISTAN - Mirzasoliev Mirzaosimjon Mirzasoypovich, Bukharov Komil Khushvaktovich, Kholmirzaev Ilhomjon Hasanbaevich (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article provides a comprehensive assessment of 10 varieties and hybrids capable of growing onions as a secondary crop in Uzbekistan and recommends the planting of promising varieties. At the same time determine the optimal planting dates for seedlings of a certain age. A correlation between important traits of this crop has been proven. Banko onions F1, Daytona F1 Scientifically based recommendations have been given to expand the cultivation of Daytonaduragaylar and Istiqbol varieties as seedlings. Timing of planting seedlings, plant placement schemes and leaf and root of onion seedlings 1/3 Elements of cultivation technology have been improved, such as sowing part of the crop. Recommendations for the correct selection of seedling age according to the timing of planting onion seedlings are given